Apolipoprotein Profiles in Very Preterm and Term‐Born Preschool Children. Issue 8 (16th April 2019) - Posod, Anna; Pechlaner, Raimund; Yin, Xiaoke; Burnap, Sean Anthony; Kiechl, Sophia Julia; Willeit, Johann; Witztum, Joseph L.; Mayr, Manuel; Kiechl, Stefan; Kiechl‐Kohlendorfer, Ursula
Abstract : Background: Little is known about plasma apolipoprotein profiles in very preterm‐born and term‐born preschool children compared with the adult population. This is of particular interest because apolipoprotein composition might contribute to cardiometabolic outcome in later life. Methods and Results: Children aged 5 to 7 years born at term or with <32 weeks of gestation were included. Apolipoprotein concentrations were measured in plasma collected after an overnight fast using multiple‐reaction monitoring‐based mass spectrometry. Twelve apolipoproteins were measured in 26 former term and 38 former very preterm infants. Key findings were confirmed by assessing apolipoprotein levels using antibody‐based assays. Comparing children born term and preterm, apolipoprotein A‐I, A‐IV, C‐II, and C‐III were significantly higher in the latter group. Term‐born children showed plasma levels of apolipoprotein C‐II and C‐III quantitatively similar to the adult range (Bruneck study). Hierarchical clustering analyses suggested that a higher proportion of apolipoprotein C‐III and C‐II reside on high‐density lipoprotein particles in children than in adults given the marked correlations of apolipoprotein C‐III and C‐II with high‐density lipoprotein cholesterol and apolipoprotein A‐I in children but not adults. High‐density lipoprotein cholesterol concentrations were similar in children and adults but the pattern of high‐density lipoprotein cholesterol–associated apolipoproteins was different (lower apolipoprotein A‐I and C‐I but higher A‐II, A‐IV, and M). Conclusions: Our study defines apolipoprotein profiles in preschoolers and reports potential effects of prematurity. Further large‐scale studies are required to provide evidence whether this apolipoprotein signature of prematurity, including high apolipoprotein C‐II and C‐III levels, might translate into adverse cardiometabolic outcome in later life.